Structural and optical characterization of sol-gel derived boron doped Fe2O3 nanostructured films - Aydin, C.; Mansour, Sh A.; Alahmed, Z. A.; Yakuphanoğlu, Fahrettin (Springer, 2012)
Pure and boron (B) doped iron oxide (Fe2O3) nanostructured thin films were prepared by sol-gel spin coating method. The effects of B (0.1, 0.2, 0.5 and 1 %) content on the crystallinity and morphological properties of Fe2O3 films were investigated by X-ray diffractometer and atomic force microscopy. X-ray diffraction patterns revealed that the Fe2O3 films have a rhombohedral crystalline phase of alpha-Fe2O3 phase (hematite) with nanostructure and their crystallite size (D) is changed from 27 +/- A 2 to 45 +/- A 5 nm with B dopant content. The minimum crystallite size value of 27 +/- A 2 nm was obtained for 0.2 % B doped Fe2O3 film. Carrying out UV-VIS absorption study for both doped and undoped films at room temperature, it was realized that allowed optical transitions may be direct or indirect transitions. The direct and indirect energy gap values for pure Fe2O3 were obtained to be 2.07 and 1.95 eV, respectively. The optical band gap value of the films was changed with 0.1 % B doping to reach 1.86 eV for direct band gap and 1.66 eV in case of indirect band gap.
Keywords: Nanostructure; Sol-gel; Hematite Fe2O3; Optical properties